Testing the Caregiver Stress Model with the Caregivers of Hemodialysis Patients - Aktas, Aysenur; Sertel-Berk, H. Ozlem (ISTANBUL UNIV, FAC LETTERS, DEPT PSYCHOLOGY, 2019)
Chronic renal failure (CRF) is a long, progressive, and chronic condition that requires care. In hemodialysis treatment, which is the most preferred treatment method in CRF, caregivers (informal caregivers) and health teams (formal caregivers) have difficulties as much as patients during the period of illness, and treatment. The aim of this study is to investigate the caregiving process of hemodialysis patients' informal and formal caregivers within the frame of the ``Caregiver Stress Model{''}. Informal (N = 50, mean of age: 48.5, 92\% of which were woman), and formal (N = 63, mean of age: 33.4, 84\% of which were woman) caregivers from various dialysis units in Istanbul participated in the study. The Resilience Scale for Adults, The Caregiver Well-Being Scale, The Multidimensional Scale of Perceived Social Support, The Ways of Coping Inventory, and the Maslach Burnout Inventory were used. The results showed that the unconfident coping factor of The Ways of Coping Inventory was a moderator of the relationship between the vital activities and personal success which is sub-dimension of Maslach Burnout Inventory was revealed. Also, the findings suggested that resilience, self-confident and unconfident coping factors were significant mediators of the relationships between the vital activities and personal success. The importance of this study is that the caregiver stress model being tested on caregivers of hemodialysis patients has never appeared in the literature before. In the literature, psychological resilience, coping and social support variables, whose formative effects are frequently discussed, contributed to the mediator effects that partially supported the model. Our findings are discussed in light of other published studies in the field.
Keywords: Caregiving; hemodialysis; caregiver stress model; chronic renal failure